Strategy Formulation for Increasing the Social Capital of Women in Small Scale Industries - Rahel Widiawati Kimbal; Tinneke EM Sumual (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
This research aims to find a strategy formulation for strengthening women's social capital in small-scale industries. Given that the power of social capital has started to dissolve and weaken along with the current modernization, the design of a strategy should be a crucial capital in the continuation of small scale companies integrating women as pillars of the family economy. Therefore, a formulated strategy is needed to strengthen social capital in small scale industries. With a case study on the Kacang Tore small industry, this study used a qualitative research methodology. To gather data, a triangulation approach of observation, interviews, and documentation was used. The stepwise forward model developed by Spradley is used in this study's data analysis. The results identifie various strategies to strengthen women's social capital in terms of trust, networks, reciprocity, values and norms. Keywords: Formulation, Small Scale Industries, Social Capital, Strategy, Strengthening, Women